Loss of HOXA10 causes endometrial hyperplasia progressing to endometrial cancer. (26th August 2022) - Mishra, Anuradha; Ganguli, Nirmalya; Majumdar, Subeer S; Modi, Deepak
Abstract : Endometrial cancer is the fourth most common malignancy in women and the precursor lesion is endometrial hyperplasia. HOXA10 is a transcription factor that plays key roles in endometrial functions such as the endowment of receptivity, embryo implantation, and trophoblast invasion. Herein, using testicular transgenesis, we developed transgenic mice that expressed a shRNA against HOXA10 and there was a nearly 70% reduction in the expression of HOXA10 in these animals. We observed that downregulation of HOXA10 led to the development of endometrial hyperplasia in the young animals (3 months), and as they aged (>1 year), most animals developed well-differentiated endometrial adenocarcinoma. In the endometrium of animals with reduced HOXA10, there was increased proliferation and elevated levels of ERα and ERβ. In parallel, there was increased expression of Wnt4 and β-Catenin, SOX9, and YAP1. We propose that chronic reduction in HOXA10 expression disrupts multiple pathways in the uterus that aids in the development of endometrial hyperplasia which progresses to endometrial cancer with age.